PENGARUH BERMAIN PERAN TERHADAP KEMAMPUAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL 5 MATARAM - Rabiah Rabiah (Universitas Pendidikan Mandalika, 2014)
The purpose of this study was to determine the effect of role playing on the social emotional abilities of children aged 5-6 years. The research method used was an experimental method with one group pretest-postest design. The population of this study were all children aged 5-6 years at Aisyiyah Bustanul Athfal 5 Mataram Kindergarten, totaling 53. The sample in this study was taken based on a specific objective, which was class B3, totaling 18 children. The data collection method in this study was observation as a method. subject, interviews and documentation as complementary methods. The data analysis technique used the t-test formula. From the results of the t-test, where the t-test is 14.470, while the t-table value with a significant level of 5% = N-1 = (18-1) = 17 is 1.740, this fact shows that the t-test value obtained in the study This is greater than the t-table value (14,470> 1,740) which means significant. This means that the null hypothesis (Ho) is rejected while the alternative hypothesis (Ha) is accepted. The conclusions obtained in this study are: